Environmental law and policy in India :cases,materials and statutes - Divan, Shyam; Rosencranz, Armin (New Delhi, 2001)
Environmental law and policy in India affects all sections of society. The volume is interlaced with notes, comments and questions to encourage critical thinking among lawyers and law students. It compiles all the leading cases in environmental law in India with concise extracts of landmark judgments and documents. It focuses on environmental law, policy, problems and needs with the comprehensiveness of an American law case book.
Keywords: Environmental law